Analisis validitas prediktif tryout dalam mengukur kesiapan uji kompetensi mahasiswa PPG bidang studi Pendidikan Pancasila: - Sri Untari; Joko Sayono (Jurnal Praksis dan Dedikasi Sosial, 2026)
Predictive validity analysis of tryouts in measuring PPG students’ readiness for the competency test in Pancasila Education This study aims to analyze the predictive validity of tryout tests as an instrument to measure the readiness of teacher professional education (PPG) students in the field of Civic and Pancasila Education to face the Competency Examination. The research is grounded in the need to ensure that tryouts serve not only as practice tests but also as reliable indicators for projecting students’ success in the final examination. A mixed methods approach with an embedded design was employed, in which quantitative analysis was the primary focus, complemented by qualitative data for triangulation. Quantitative data were obtained from the tryout results of 279 PPG students in Civic and Pancasila Education. The analysis measured validity, reliability, difficulty level, and discriminating power of the test items. Qualitative data were collected through interviews with five purposively selected students, providing insights into the usefulness of the tryout in helping them understand the structure and model of the Competency Examination. The findings reveal that although some test items showed weaknesses in terms of validity and discriminating power, the tryout overall proved effective in enhancing students’ readiness and served as a predictive tool for success. Consequently, tryouts can be positioned as a pedagogical strategy that strengthens both academic skills and pedagogical content knowledge of future Civic and Pancasila Education teachers. Penelitian ini bertujuan untuk menganalisis validitas prediktif tes tryout sebagai instrumen untuk mengukur kesiapan mahasiswa Pendidikan Profesi Guru (PPG) bidang Pendidikan Pancasila dan Kewarganegaraan dalam menghadapi Uji Kompetensi. Penelitian ini didasarkan pada kebutuhan untuk memastikan bahwa tryout tidak hanya berfungsi sebagai tes latihan, tetapi juga sebagai indikator yang andal untuk memproyeksikan keberhasilan mahasiswa dalam ujian akhir. Penelitian ini menggunakan pendekatan metode campuran dengan desain embedded, di mana analisis kuantitatif menjadi fokus utama dan dilengkapi dengan data kualitatif sebagai triangulasi. Data kuantitatif diperoleh dari hasil tryout 279 mahasiswa PPG bidang Pendidikan Pancasila dan Kewarganegaraan. Analisis dilakukan dengan mengukur validitas, reliabilitas, tingkat kesukaran, dan daya pembeda butir soal. Data kualitatif dikumpulkan melalui wawancara dengan lima mahasiswa yang dipilih secara purposif. Data tersebut memberikan gambaran mengenai manfaat tryout dalam membantu mahasiswa memahami struktur dan model Uji Kompetensi. Temuan penelitian menunjukkan bahwa meskipun beberapa butir soal masih memiliki kelemahan dari segi validitas dan daya pembeda, secara keseluruhan tryout terbukti efektif dalam meningkatkan kesiapan mahasiswa dan berfungsi sebagai alat prediktif terhadap keberhasilan. Dengan demikian, tryout dapat diposisikan sebagai strategi pedagogis yang memperkuat keterampilan akademik sekaligus pengetahuan konten pedagogis calon guru Pendidikan Pancasila dan Kewarganegaraan.